Green Public Transport in Poland—Planning the Process of the Electrification of the Bus Fleet of Vehicles - Norbert Chamier-Gliszczynski; Adam Wyszomirski; Cezary Balewski; Michał Kłodawski (Energies)
The concept of green public transport in Poland is a challenge posed to Polish cities, which reflects the AFIR (Regulation for the Deployment of Alternative Fuels Infrastructure) regulation and the amended Polish Law on Electromobility and Alternative Fuels. The fulfillment of the established prerequisites requires taking steps toward the implementation of the electrification process of the fleet of bus vehicles. The goal of this process is to replace the fleet of buses equipped with internal combustion engines (conventional buses) with zero-emission buses. In the category of zero-emission vehicles, we distinguish between electric-powered buses (electric buses), hydrogen-powered buses (hydrogen buses) and trolleybuses. It is forecast that such exchanges will be spread out over time and may last 16 to 20 years. Thus, an important element in these activities is planning, which, as a process, leads to the establishment of tasks, resources and activities aimed at realizing or achieving the desired goal. It was assumed that the purpose of the article is to present the essence of planning the process of electrification of the bus fleet of vehicles in Polish cities. The content of the article refers to the concept of planning the process of electrification of the bus fleet of vehicles in urban areas, taking into account economic aspects, sources of financing and analysis of the feasibility of this process on the example of a selected Polish city. The planning process was presented using the example of a city integrated with the surrounding nature. The choice of the city is not accidental because the analyzed urban area lies in the green part of the West Pomeranian Voivodeship, in the vicinity of which there are four nature reserves. The city is situated on two lakes, which together occupy 11.2% of the city’s area, and there are also numerous green areas in the city. The green nature of the city argued for taking action to reduce local emissions of pollutants generated by public transport. The process of planning the electrification of the bus fleet was carried out based on environmental and economic aspects. In economic terms, an important element is the possibility of obtaining external financing and the analysis of the feasibility of the planned process of electrification of the bus fleet. The conducted research clearly indicated that the presented process of planning the electrification of the bus fleet in the selected urban area allows for a precise interpretation of the considered planning in environmental and economic terms. Such an interpretation is important for the evaluation process of the analyzed planning and the implementation of the concept of green public transport in Polish cities, as well as the transparency of this process to other European cities and beyond.